Disability as a diversity and inclusion factor in recruiting - Toyin Solomon OLANIYAN; Kayode Wakili OLAWOYIN; Isaac Ojo OKUNADE (Acta Politica Polonica)
Above all, the population of individuals with impairments is constantly increasing, making them one of the largest groups in the diverse workforce. Jobs for people with impairments requires the implementation and development of special processes within enterprises. This is because the details of employment of persons with disabilities must be considered organizationally and legally. Examining current diversity and inclusion policies of companies and states concerning the hiring of people with disabilities is the aim of this research. According to the study's findings, there were no appreciable variations between employees with disabilities and those without them at various phases of the hiring process. Nonetheless, it should be noted that corporate behavior regarding the employment of persons with disabilities is largely influenced by the Nigerian legal system.